PENGGUNAAN MEDIA FILM UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK (LISTENING) BAHASA INGGRIS BAGI SISWA KELAS XII P MIPA 1 SMA NEGERI 1UBUD PADA SEMESTER 1 TAHUN PELAJARAN 2017/2018 - Ni Nengah Budiasih (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
This action-based research was conducted as the implementation of a new learning model by using film as a media to improve students’ ability in listening of English of class XII P MIPA 1 SMA Negeri 1 Ubud in semester I of the academic year 2017/2018. The class which is consisted of 35 students were chosen as the subject of this research were due to the result of the pre-test shown that 65,81 were still far below the school standard of 75. The object of this research is the ability of listening English which is known as the main obstacle in learning English. This research was conducted in 2 cycles from July to September 2017. The data obtained by using tes of listening. The data was analyzed to find out the students’ listening score (Mean) and the classical learning mastery. The research shows that the use of film as a learning media was effective in improving the students’ listening ability. In the pre-test, the percentage of the students’ ability was 65,81%, while in the first and second cycles were 75,52 % and 79,43. It can be concluded that the use of film as a learning media was effective in improving the students’ability in listening of English of class XII P MIPA 1 of SMA N 1 Ubud at semester 1 in the academic year of 2017/2018 Eventhough.